Analisis Produktivitas Tukang terhadap Beban Kerja pada Pekerjaan Jalan - Kiki Rizky Amalia; Seprisal Seprisal (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Human resources (labor) are the most difficult factors predicted by productivity because they have very many variables, both internal (age, ethnicity, experience, motivation, education) and external ones (composition of work groups, environment, supervision, system payroll). Labor is an expensive resource, and is a factor of production that contributes greatly to the completion of the project, because it is the workforce that manages and controls the material and work equipment. In this study the survey began from September 2017 to December 2017. The survey was conducted on the Sei. Saren-Teluk Nilau-Senyerang-Batas Riau road project. To complete the survey survey data carried out on 12 people who were scattered and 12 people pembesian, in which the masons are accustomed to doing their work with work experience that has been obtained, which each observation is done three working days, with three times a day for 30 minutes in one day. In artisan research, the productivity volume produced by artisans varies considerably between the first, second and third days, but the difference in productivity is not much different. This can be seen from the results of research which show that the average productivity produced on the first day is 0.64 M2 / minute, while on the second day the resulting productivity is 0.59 M2 / minute and on the third day is 0.85 M2 / minute. This data shows that the productivity produced every day is not much different. In this observation, it can also be seen the artisan productivity figures produced for three days with a variety of data collection in the morning, afternoon and evening, where the average value of productivity for three days is 0.69 M2 / minute and 16.5 M2 / artisan .